PENERAPAN METODE READING ALOUD UNTUK MENINGKATKAN KEMAMPUAN MEMAHAMI BACAAN SISWA KELAS IV SDN 128 PEKANBARU - BR Sembiring, Lidia BR Sembiring; Witri, Gustimal; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research based by observations of the authors in SDN 128 Pekanbaru, there are phenomena or symptoms of low reading scores of fourth grade students of SDN 128 Pekanbaru, which still have not reached the minimum completeness criteria (KKM) set school students is 70. Of the 28 people were only 6 students, or 21% who have reached KKM. According to the background and the formulation of the problem, the study aims to determine the application method of reading aloud to improve reading comprehension fourth grade students of SDN 128 Pekanbaru. This research was conducted in the fourth grade SDN 128 Pekanbaru, while the time the study was conducted in the academic year 2015/2016. Design of this research is the Classroom Action Research (PTK). As the subjects in this study were teachers and students of class IV SDN 128 Pekanbaru with 28 students, consisting of 12 men and 16 women. The conclusion from this study is there is an increased ability to understand the reading at the fourth grade students at SDN 128 Pekanbaru by applying the method of reading aloud. Increasing the value of the average student pda base score is 62,29 increased to 71,61 and increased again to 78,04 in the second cycle. In the first cycle obtained an increase of 9,32 from a base score or an increase of 14,96%. Then in the second cycle is obtained an increase of 15,75 from a base score or an increase of 25,28%.Key words: Reading Aloud, Reading Comprehension Abilities